334.75(575.16) ISSUES OF DEVELOPING WOMEN'S ENTREPRENEURSHIP - Zulfikarova, Dilfuza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The organization and promotion of women's entrepreneurship are the wishes, desires, and main goals of leaders around the world. The reason is that women's entrepreneurship has its rightful place in the socio-economic development of the country. In the republic, special attention is paid to the organization and development of entrepreneurial entities, which are the drivers of the national economy, the problems associated with them, and their solutions. It is noteworthy that the state is creating a number of facilities and opportunities in this regard. From this point of view, the article highlights the importance, necessity, and relevance of the effective organization and development of women's entrepreneurship. A number of factors contributing to the development of women's entrepreneurship in the country, including the decrease in the number of registered marriages in recent years, the increase in divorces, the prevalence of cardiovascular diseases among people's deaths, the increase in the level of labor migration of the population, and similar factors.